The Effect of Working Capital Management and External Capital on Going Concern for Indonesian Small and Medium Enterprises - Widya Exsa Marita; Ika Permatasari (AKRUAL: JURNAL AKUNTANSI, 2019)
This study aimed to examine the influence of working capital management and external capital ongoing concern of small and medium enterprises in Indonesia. This study used small and medium listed enterprises in Indonesia as a sample, which were included in the Pefindo-25 index from the year 2009-2016. The results showed that working capital management had a negative effect on SMEs going concern, while the external capital had a positive effect. This study had the implication for small and medium-sized issuers, which was they were expected to be able to accelerate the company's cash conversion cycle to improve working capital management so as to improve the sustainability of their business. In addition, they were expected to consider external capital as an alternative capital to increase competitiveness in the market.